2015
DOI: 10.1016/j.egypro.2015.11.264
|View full text |Cite
|
Sign up to set email alerts
|

A Study on the Contaminant Dispersion from Isolation Ward under Abnormal Operation of Facilities

Abstract: Due to the recent outbreaks of infectious diseases, such as severe acute respiratory syndrome (SARS), Influenza and Ebola, isolation facilities have played an important role to prevent infectious diseases from spreading at initial stage. An isolation ward is a facility to isolate patients physically and to care them safely. One way to isolate a patient physically is to build a negative pressure isolation facility. However, unexpected failure or misuse of such facility makes it difficult to maintain negative pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…The normal operation of ventilation system is the premise to ensure the airflow isolation effect. Park J Y et al conducted a tracer gas experimental study, and the results showed that the failure or abnormal operation of ventilation equipment in the isolation ward would lead to the spread of infectious bacteria to the human body and the risk of infection [ 38 ]. Therefore, the ventilation system needed to be equipped with an alarm system and a reasonable control program.…”
Section: Purification and Disinfection And Ventilation System Controlmentioning
confidence: 99%
“…The normal operation of ventilation system is the premise to ensure the airflow isolation effect. Park J Y et al conducted a tracer gas experimental study, and the results showed that the failure or abnormal operation of ventilation equipment in the isolation ward would lead to the spread of infectious bacteria to the human body and the risk of infection [ 38 ]. Therefore, the ventilation system needed to be equipped with an alarm system and a reasonable control program.…”
Section: Purification and Disinfection And Ventilation System Controlmentioning
confidence: 99%
“…Due to its provision, it must remain closed continually. To test the hypothesis, Park and Sung ( 2015 ) selected a patient ward to determine the amount of leakage air through tracer gas tests and CFD methods. Chow et al ( 2006 ) numerically assessed the effects of the pressure differential between the inside and outside of an operating room on the airflow characteristics.…”
Section: Current Assessment Of Airflow and Particle Concentration In ...mentioning
confidence: 99%